The effect of metformin on vertebral marrow fat in postmenopausal women with newly diagnosed type 2 diabetes mellitus. Issue 3 (March 2020) - Lin, Fang; Pan, Yuning; Zhang, Yinwei; Zhou, Qiang
Abstract: Objective: To determine the effect of metformin on marrow adiposity in postmenopausal women with newly diagnosed type 2 diabetes mellitus (T2DM). Methods: We enrolled 25 postmenopausal T2DM women who satisfied the requirement of having been on 1 year of metformin therapy and 26 age-matched healthy women receiving a placebo. All participants were analyzed for marrow fat fraction (FF) by magnetic resonance spectroscopy, vertebral volumetric bone mineral density (vBMD) by quantitative computed tomography, blood glucose, lipid profiles, and bone biomarkers to compare values before and after the interventions. Differences between groups were assessed using a Student's t test and chi-square test or an analysis of covariance adjusted for covariates. Twelve-month change in within-group difference was assessed using paired t tests. Correlations were determined by Pearson's correlation. Results: Vertebral vBMD was lower in T2DM than in nondiabetic controls (105.6 ± 13.8 vs 112.8 ± 15.2 mg/cm 3 ; P = 0.029). T2DM women had a higher marrow FF than those without diabetes (66.3 ± 7.2% vs 58.9 ± 7.5%; P < 0.001), even after adjusting for covariates. From baseline to month 12 in the T2DM group, metformin was associated with a reduction in marrow FF (−12.0%; P < 0.001) and an increase in vBMD (3.7%; P = 0.020). For metformin-treated T2DM women, the 12-month change in marrow FF was inversely associated with change in vBMD ( r = −0.771, P < 0.001), but not with changes in bone biomarkers, whereas change in vBMD or FF was not significant in the control group. Conclusion: Postmenopausal women with newly diagnosed T2DM have a higher marrow fat content compared with nondiabetic women. Metformin treatment reduced marrow adiposity in T2DM.